The impact of public spending on economic growth in Morocco from 1960 to 2022: An ARDL bounds approach - Aissaoui, Zineb El; Dkhissi, Atman; HDA, Mounia (Asian Journal of Economic Modelling, 2024)
The impact of public spending on economic growth is a major topic in macroeconomics that has been debated for a long time. This debate has recently intensified particularly in the Moroccan context. This research examines how public spending has affected economic growth in Morocco from 1960 to 2022. To achieve this objective, we have selected a quantitative approach with an econometric analysis to assess the variables in question. Research methodology employs the Autoregressive Distributed Lag (ARDL) bounds testing approach. This study analyzes at a time the short- and long-run effects of public spending on economic growth using time-series data. The study’s findings indicate a significant and positive impact of public expenditures on economic growth both in the short- and long- run. The results of this study are consistent with earlier studies despite using different variables that support the validity of our findings. Our research provides robust insights into the dynamics of public spending and economic growth in Morocco by spanning such an extensive period. The ARDL bounds testing approach allows for a nuanced understanding of the immediate and delayed effects of public expenditures. The findings of this research underscore the importance of public spending in fostering economic growth and highlight the potential benefits of maintaining or increasing such expenditures.